The Implementation of Performance Management in the Regional Office of the Ministry of Religious Affairs, Gorontalo Province - Tilome, Arfan A (Universitas Muhammadiyah Gorontalo, 2025)
This study aims to determine the implementation of performance management within the Regional Office of the Ministry of Religious Affairs in Gorontalo Province. As a public service institution, the Regional Office of the Ministry of Religious Affairs in Gorontalo Province is mandated to adopt contemporary principles and functions of performance management in order to effectively address public needs and realize the organization’s established objectives. To the best of current knowledge, no scholarly investigation has yet examined the implementation of performance management within the context of this Regional Office. This research, therefore, seeks to address this critical gap, underscoring its scholarly and practical significance. Performance management is examined using two models: the cycle model and the sequence model. Each model examines several aspects, including strategic plan formulation, work agreements, work actions and development, monitoring and feedback, formal reviews, and performance assessments. The research used field research, where the researcher directly observed and participated in almost all performance management processes within the Regional Office of the Ministry of Religious Affairs in Gorontalo Province. The results of this study reveal that the Regional Office of the Ministry of Religious Affairs in Gorontalo Province has generally implemented performance management processes effectively. There are only a few aspects that require improvement and refinement, namely the follow-up of evaluation results and the implementation of employee development, which should be carried out in a planned, structured, and periodic manner.